Sustainable Development Goal: The East Nusa Tenggara Poverty Analysis - Hudaya, Afaqa; Saputro, Dio Bimo (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Poverty is the thorny issue that occurs every year in East Nusa Tenggara Province. Poverty alleviation is identified as one of the main goals of the Sustainable Development Goals (SDGs). Various steps have been taken to achieve this goal. One of the factors that trigger the increase in poverty is inadequate access to the fulfillment of the community's basic needs. This study aims to analyze the impact of limited access to basic community needs on poverty in East Nusa Tenggara using an empirical approach. Accessibility to basic needs is measured through variables such as life expectancy at birth, per capita expenditure, average years of schooling, and expected years of schooling. This study uses panel data analysis technique using fixed effect model. The findings of this study show that improvements in these variables, namely life expectancy at birth, per capita expenditure, and expected years of schooling, contribute to poverty alleviation in East Nusa Tenggara. Limited access to health services has an adverse impact on life expectancy at birth. Conversely, high levels of employment are expected to increase per capita expenditure in East Nusa Tenggara, thereby improving welfare and reducing poverty levels.